2021
DOI: 10.1002/cjce.24267
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of nanofluids forced convection in a corrugated double‐pipe heat exchanger

Abstract: In this study, the heat transfer and flow characteristics of TiO2‐H2O nanofluids with TiO2 mass fractions of 0.0, 0.1, 0.3, and 0.5 wt.% in corrugated and smooth double‐pipe heat exchangers were compared using numerical simulations. The results demonstrated that TiO2‐H2O nanofluids effectively enhanced the heat transfer compared to deionized water, and that the heat exchange capacity gradually increased with the TiO2 mass fraction. The corrugated pipe heat exchanger disturbed the fluid flow on both the shell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In fact, the use of corrugated tube of heat transfer fluid is also an effective way because that the corrugated surface has the function of expanding the heat transfer surface. The advantage of corrugated tube in heat exchanger without PCM has been proved by many authors (Wang et al, 2016;Li et al, 2017;Ding et al 2022). Zhang et al (2020).…”
Section: Introductionmentioning
confidence: 98%
“…In fact, the use of corrugated tube of heat transfer fluid is also an effective way because that the corrugated surface has the function of expanding the heat transfer surface. The advantage of corrugated tube in heat exchanger without PCM has been proved by many authors (Wang et al, 2016;Li et al, 2017;Ding et al 2022). Zhang et al (2020).…”
Section: Introductionmentioning
confidence: 98%
“…The mesh was refined in each case until it reached a point where the results were not noticeable. Figure (5) shows that the variation in the temperature is not significant with the increase in the number of elements. The number of elements (4788691) was found to be appropriate for the current study.…”
Section: Mesh Generation and Grid Independencymentioning
confidence: 92%
“…In the current work, the unstructured mesh of tetrahedron and wedges were used and take notice of wedges elements which are positioned near the walls using inflation layers [12]. Figure (4) shows the mesh of the full model while figure (5) shows the grid independence test was achieved in the reliability of mesh because the poor design of the grid may lead to a decrease in the accuracy of the simulation results. The mesh was refined in each case until it reached a point where the results were not noticeable.…”
Section: Mesh Generation and Grid Independencymentioning
confidence: 99%
See 1 more Smart Citation
“…Ding et al carried out a numerical simulation of TiO 2 -water nanofluids in a double-pipe heat exchanger considering various flow rates and TiO 2 mass fractions. The results demonstrated that the heat transfer capacities of all mass fractions of TiO 2 -water nanofluids were higher than those of deionized water, but they also increased the flow resistance in a corrugated pipe [ 9 ]. Akbar et al achieved excellent results employing a hybrid nanofluid (Al 2 O 3 +TiO 2 -water) to improve the heat transfer and pressure drop through horizontal tubes with diameter sizes of 30 to 45 nm.…”
Section: Introductionmentioning
confidence: 99%